(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This study reorganizes and conceptualizes existing patent strategy research, which has origins in a variety of fields such as economics, law, and management. As a result, it is expected that this analysis will assist to organize and drive what is now a disjointed and fragmented area of management research. The primary framework presented focuses on two key topics in patent strategy research: generic patent strategies and patent strategic management. Furthermore, research in each of these topics is usually mapped onto one or more of three major domains—rights, licensing, or enforcement—within which patent-related strategic activities are normally carried out. The three patent strategy domains are juxtaposed with various theoretical lenses used in patent strategy research in two summary tables of previous research. Finally, the paper discusses two potential areas where research is starting to focus on their links to patent strategy: companies’ general appropriability strategies and value creation strategies. An overall conceptual graphic depicts the many study topics discussed in the article and emphasizes the connections between them. By revealing its numerous connections with the wider management field and providing possibilities to address key unsolved research issues, the reconceptualization and reframing of previous research presented in this study promises to improve scholarship on patent strategy. As a result, it serves as a helpful road map for future management study in this critical field.